Mediating factors and spillover effects of foreign direct investment : Evidence from Indian manufacturing firms - Bikash Ranjan Mishra; Lopamudra D. Satpathy; Pabitra Kumar Jena; Tania Dehury (Heliyon, 2024)
The present study examines the extent and direction of horizontal, backward and forward spillover effects of FDIs on firms' productivity. It also shows how the mediating factors (firm's age, export and import intensity, R&D and advertisement intensity) contribute to the firms' productivity. Further, the study also uncovers the importance of the ownership patterns of the firms that affect the spillovers. It uses a balanced firm-level panel data set from the Indian manufacturing industries over the available period 2003 to 2016 to examine the inter- and intra-industry spillovers of the FDIs. The estimation methods used in this study are the fixed effects approach and the generalised method of moments. The study also applies the Levinsohn-Petrin method to compute firm-level productivity. It finds a significant positive spillover backward effect and confirms the supportive role of the mediating factors in augmenting the spillover channels. However, the results do not support the existence of horizontal and forward FDI spillover effects for the overall manufacturing industries. They suggest that a comprehensive policy package approach be used, thereby underlining the importance of all channels of the FDI spillover effects and their relations to the downstream sector, particularly by keeping the performance of the firms and their external links in perspective.